Incidence and Patterns of Abuse among Patients aged 60 years and older Attending the Consultation Clinics in Al-Imam Hussein Medical City in Karbala Governorate, 2020: Patterns of elder abuse - Abdul-Abbas, Zainab Badri; Baydaa Ibrahim Salman; Ahmed J. Al-karaqully (Karbala Journal of Medicine, 2022)
Background: Elder abuse is defined by the World Health Organization in Europe as a single or repeated act, or lack of appropriate action, occurring within any relationship where there is an expectation of trust, which causes harm or distress to an older person. It is an important cause of morbidity and mortality in developing and developed countries. Subjects and Methods: A cross-sectional study conducted included 402 patients attended the Consultation Department of Imam Hussein Medical City aged 60-year-old and over. A structured modified questionnaire was developed for the study and filled out by a doctor using face-to-face interviews. Objective: To evaluate the proportion of elder abuse, identify its different patterns, and determine the risk factors related to the problem. Results: Out of 402 total respondents, females constituted 52% (70.1%) were married, the proportion of all types of abuse/neglect was 82.1%, psychological abuse accounted for three-quarters of the study participants (74.1%), followed by physical abuse, financial abuse, and neglect (61.9%, 53.7%, and 45.8% respectively), while sexual abuse reported by only 4% participants. In general, the main three perpetrators of all types of abuse were spouses, followed by a son and daughter (41.8%, 38.1%, and 21.9%), respectively. Conclusion: The proportion of elder abuse is high in Karbala, with psychological abuse being the most commonly reported pattern, the abuse induced by a family member in most of the cases, and two-thirds of the study participants did not report the abuse.